Lithium secondary battery
By using a composite oxide of lithium and transition metal as the positive electrode active material in a lithium secondary battery, and laying an insulating porous film on the negative electrode, the problem of dendrite precipitation of lithium metal tree is solved, and the discharge capacity and cycle characteristics of the battery are improved.
Patent Information
- Application Number
- CN201980047592.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-07-30
- Filing Date
- 2019-07-05
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2039-07-05
AI Technical Summary
When the lithium secondary battery is charged, lithium metal is precipitated in dendrite form, resulting in an increase in the specific surface area of the negative electrode, an increase in side reactions, and a decrease in discharge capacity and cycling characteristics.
A separator between the positive electrode and the negative electrode is used, and the positive electrode contains a composite oxide of lithium and a transition metal as the positive electrode active material. The negative electrode has a negative electrode current collector and a plurality of insulating porous films laminated thereon to ensure that the precipitation position of lithium is between the surface of the negative electrode current collector and the porous film.
It effectively suppresses dendrite precipitation of lithium metal, reduces the expansion of the negative electrode, and improves the discharge capacity and circulation characteristics.
Smart Images

Figure CN112514129B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to improvements in lithium secondary batteries. Background Art
[0002] Non-aqueous electrolyte secondary batteries are used in ICT applications such as personal computers and smart phones, in-vehicle applications, and power storage applications. In such applications, non-aqueous electrolyte secondary batteries are required to have a further high capacity. As a high-capacity non-aqueous electrolyte secondary battery, a lithium-ion battery is known. The high capacity of a lithium-ion battery can be achieved by combining alloy active materials such as graphite and silicon compounds as negative electrode active materials. However, the high capacity of lithium-ion batteries has gradually reached its limit.
[0003] As a non-aqueous electrolyte secondary battery with a high capacity exceeding that of a lithium-ion battery, a lithium secondary battery (lithium metal secondary battery) is promising. In a lithium secondary battery, lithium metal is precipitated at the negative electrode during charging, and the lithium metal dissolves in a non-aqueous electrolyte during discharge. In a lithium secondary battery, lithium metal is precipitated in the form of dendrites on the negative electrode during charging. Moreover, as dendrites are generated, the specific surface area of the negative electrode increases, and there is a situation where side reactions increase. Therefore, the discharge capacity and cycle characteristics are prone to decrease.
[0004] Patent Document 1 teaches that, in order to suppress the growth of dendrites, a protective film made of a lithium ion conductive polymer material is provided on a negative electrode containing lithium.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2015 / 030230 Summary of the invention
[0008] The method of Patent Document 1 has the following problems: during charging, lithium metal is precipitated between the protective film and the separator. In addition, when the charge and discharge cycles increase, the protective film as described above tends to deteriorate, so lithium may precipitate in the form of dendrites and pierce the protective film.
[0009] In view of the above, one aspect of the present invention relates to a lithium secondary battery, which comprises a positive electrode, a negative electrode, a lithium ion conductive non-aqueous electrolyte, and a separator disposed between the positive electrode and the negative electrode, wherein the positive electrode comprises a positive electrode current collector and a positive electrode mixture layer containing a positive electrode active material, wherein the positive electrode active material comprises a composite oxide containing lithium and a transition metal, and the total amount of lithium per unit area of the positive electrode and the negative electrode is M Li The transition metal amount M per unit area of the positive electrode TM Molar ratio: M Li / MTM is 1.1 or less, and the negative electrode includes a negative electrode current collector and a plurality of insulating porous films stacked on the negative electrode current collector.
[0010] According to the lithium secondary battery of the present invention, the deposition of lithium in the form of dendrites is suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is a cross-sectional view schematically showing a negative electrode of a battery immediately after assembly according to one embodiment of the present invention.
[0012] Figure 2 It is a cross-sectional view schematically showing a negative electrode in a charged state according to one embodiment of the present invention.
[0013] Figure 3 It is a longitudinal cross-sectional view schematically showing a lithium secondary battery according to an embodiment of the present invention.
[0014] Figure 4A This is a diagram showing a SEM image (magnification: 2500 times) of the cross section of the negative electrode produced in Example 1 after charging.
[0015] Figure 4B To enlarge the Figure 4A A magnified view of a portion of the SEM image.
[0016] Figure 5 This is a diagram showing a SEM image (magnification: 2500 times) of the cross section of the negative electrode produced in Comparative Example 1 after charging. DETAILED DESCRIPTION
[0017] The lithium secondary battery of this embodiment comprises a positive electrode, a negative electrode, a lithium ion conductive non-aqueous electrolyte, and a separator disposed between the positive electrode and the negative electrode. The positive electrode comprises a positive electrode current collector and a positive electrode mixture layer comprising a positive electrode active material. The positive electrode active material comprises a composite oxide containing lithium and a transition metal. The negative electrode comprises a negative electrode current collector and a plurality of insulating porous films stacked on the negative electrode current collector.
[0018] Here, the total amount M of lithium per unit area in the positive electrode and the negative electrode is Li The amount of transition metal per unit area of the positive electrode M TM Molar ratio: M Li / M TM is less than 1.1. That is, the negative electrode does not substantially have lithium metal that can be discharged just after assembly. In other words, the negative electrode has a negative electrode collector but may not have a negative electrode active material layer. As a result, the volume energy density of the battery is improved. It should be noted that in the fully discharged state, the molar ratio: M Li / M TM It is also below 1.1.
[0019] The fully discharged state of a lithium secondary battery refers to a state in which the battery is discharged to a charge state (SOC) of 0.05×C or less when the rated capacity of the battery is C. For example, it refers to a state in which the battery is discharged to a lower limit voltage at a constant current of 0.05 C. The lower limit voltage is, for example, 2.5V to 3.0V.
[0020] In a lithium secondary battery, lithium metal is deposited on the surface of the negative electrode collector by charging. More specifically, by charging, the lithium ions contained in the non-aqueous electrolyte accept electrons on the negative electrode collector to become lithium metal, and are deposited on the surface of the negative electrode collector. According to the negative electrode of this embodiment, the deposition position of the lithium metal can be controlled to be between the surface of the negative electrode collector and the porous membrane. Therefore, dendrites are suppressed. As a result, it becomes easy to suppress the expansion of the negative electrode caused by the deposition of lithium metal.
[0021] The reason why the precipitation position of lithium metal is controlled is still uncertain, but it is speculated as follows. The multiple porous membranes possessed by the negative electrode are formed in a way that they are in contact with each other. These porous membranes all have through holes that penetrate their respective main surfaces. Therefore, the lithium ions contained in the non-aqueous electrolyte reach the surface of the negative electrode collector through the through holes possessed by each porous membrane, and accept electrons. Among them, there are at least two layers of porous membranes in the present embodiment, so the positions of the through holes possessed by each porous membrane are mostly staggered, and there are almost no through holes that penetrate all the porous membranes at the same time. Therefore, even if the lithium metal generated by accepting electrons from the negative electrode collector enters the through holes of the porous membrane (such as the second porous membrane described later) configured on the negative electrode collector side, it cannot enter the through holes of the porous membrane (such as the first porous membrane described later, and the third porous membrane) configured on the separator side. As a result, the precipitation of lithium metal on the surface of the outermost porous membrane opposite to the separator is suppressed.
[0022] Moreover, each porous film is insulating. Therefore, only the lithium ions that reach the surface of the negative electrode collector accept electrons and precipitate lithium metal there. Thus, the precipitation of lithium metal inside the through-holes of the porous film disposed on the negative electrode collector side is also suppressed. As a result, the precipitation position of lithium metal is controlled between the surface of the negative electrode collector and the porous film disposed on the negative electrode collector side.
[0023] Furthermore, since there are multiple porous films, the movement distance of lithium ions is increased, and lithium ions are easily diffused along the surface direction of the negative electrode current collector. Therefore, the concentration of lithium metal deposition sites is alleviated, and lithium metal is easily deposited in a dispersed and bulk form.
[0024] Usually, the negative electrode is larger than the positive electrode, and part of the main surface of the negative electrode collector is not opposite to the positive electrode mixture layer. Lithium metal is easily precipitated in the part of the negative electrode collector opposite to the positive electrode mixture layer. Therefore, each porous membrane can have a region (opposite region) opposite to the positive electrode mixture layer.
[0025] From the viewpoint of enhancing the effect of suppressing dendrites, at least one porous film may have a non-opposing region not opposing the positive electrode mixture layer in addition to the opposing region. At least one porous film may be formed on the entire main surface of the negative electrode current collector opposing the positive electrode.
[0026] In the case where at least one layer of the porous membrane has a relative region and a non-relative region, the contact between the non-relative region of any porous membrane and the negative electrode collector is maintained in the charged state. Therefore, the spacing distance between the relative region of the porous membrane arranged on the negative electrode collector side and the negative electrode collector is limited, and the lithium metal is precipitated under moderate compression. The reason for suppressing the growth of dendrites by compression is still uncertain, but it is speculated as follows. When lithium metal is precipitated, the growth of lithium metal is restricted in the thickness (Z axis) direction of the negative electrode collector, but there is no restriction in the surface (XY plane) direction of the negative electrode collector. Therefore, compared with the case where lithium metal can grow freely in three dimensions along the XY plane direction and the Z axis direction, lithium ions are difficult to diffuse in the Z axis direction, and the tendency to suppress the growth of dendrites is strengthened. In addition, physically, the growth of lithium metal in the Z axis direction is also hindered.
[0027] Figure 1 This is a cross-sectional view schematically showing the negative electrode of the battery of this embodiment immediately after assembly. Figure 2 It is a cross-sectional view schematically showing the negative electrode in a charged state according to the present embodiment. Figure 2 In the embodiment, the non-opposing regions are arranged at both ends of the negative electrode current collector 21. The illustrated example shows the developed state of the negative electrode. In addition, the through holes are omitted.
[0028] The negative electrode 20 includes a negative electrode current collector 21, a first porous film 22A disposed on the separator side, and a second porous film 22B disposed between the first porous film 22A and the negative electrode current collector 21. Figure 1 As shown, the first porous membrane 22A is in contact with the second porous membrane 22B, and the second porous membrane 22B is in contact with the negative electrode current collector 21 .
[0029] When charging a lithium secondary battery, Figure 2As shown, lithium metal (Li) is precipitated between the negative electrode current collector 21 and the second porous film 22B. However, the contact between the non-relative regions of the negative electrode current collector 21 and the second porous film 22B is maintained. Therefore, as mentioned above, the spacing distance between the relative regions of the negative electrode current collector 21 and the second porous film 22B is limited, and the lithium metal Li is precipitated when being appropriately squeezed. It should be noted that, even in the charged state, the contact between the first porous film 22A and the second porous film 22B is maintained.
[0030] The structure of the lithium secondary battery will be described in detail below.
[0031] (negative electrode)
[0032] The negative electrode is an electrode that precipitates lithium metal when charged. The lithium metal precipitated on the surface of the negative electrode collector is dissolved in the non-aqueous electrolyte in the form of lithium ions by discharge. The precipitated lithium metal comes from the lithium ions in the non-aqueous electrolyte. The lithium ions contained in the non-aqueous electrolyte can be lithium ions from a lithium salt added to the non-aqueous electrolyte, or lithium ions supplied by the positive electrode active material by charging, or both. In addition, it can be a lithium salt from a raw material (described later) used in the manufacture of the porous membrane.
[0033] The negative electrode includes a negative electrode collector and a plurality of porous films. The porous films are all insulating and have at least one through hole that penetrates from the main surface of the separator side to the main surface of the negative electrode collector side. The porous film is arranged on at least one main surface of the negative electrode collector. The interface can be confirmed at the boundary of each porous film, but it is difficult to separate them. However, the porous film and the separator can be separated.
[0034] The insulating material constituting the porous membrane is not particularly limited, and examples thereof include fluororesins such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), copolymers of vinylidene fluoride and hexafluoropropylene (VdF-HFP), copolymers of vinylidene fluoride and trifluoroethylene (VdF-TrFE); polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, carbamate resins, polycarbonate resins, epoxy resins, etc. Among them, from the viewpoint of swelling relative to non-aqueous electrolytes, the protective film preferably includes a fluororesin having a unit (-CH2-CF2-) from vinylidene fluoride. As such insulating materials, PVdF, VdF-HFP, VdF-TrFE, etc. can be cited.
[0035] The diameter of the through hole is not particularly limited as long as it is a degree that lithium ions can pass through. The average diameter of the through hole can be, for example, in the range of more than 100nm and less than 1000nm, and can be in the range of more than 200nm and less than 800nm. The size relationship between the through hole (the first through hole) of the porous film (the first porous film) configured on the separator side and the through hole (the second through hole) of the porous film (the second porous film) configured on the negative electrode collector side is also not particularly limited. From the perspective of easily controlling the precipitation position of lithium metal, the average diameter of the second through hole can be smaller than the average diameter of the first through hole.
[0036] The average diameter of the through hole is: the average value of the through holes contained in the area of 2 mm square when the main surface of the porous film is observed from the normal direction of the main surface of the porous film. The average diameter of the through hole can be calculated by the cross section of the thickness direction of the negative electrode. For example, any 10 through holes are selected from the cross section of the length 10 mm in the thickness direction of the negative electrode, and the average value of their width is obtained as the average diameter of the through hole. The width of the through hole is the length in the direction perpendicular to the thickness direction of the negative electrode. In the determination of the width of the through hole, a scanning electron microscope (SEM) can be used.
[0037] The thickness of the porous film is not particularly limited. However, from the viewpoint of high capacity, it is desirable that the thickness of the porous film as a whole is not too large. On the other hand, it is desirable that the porous film has a thickness that can withstand the expansion and contraction degree of the negative electrode associated with charge and discharge. The thickness of the porous film as a whole can be, for example, 0.1 μm or more and 5 μm or less, or 0.5 μm or more and 2.5 μm or less. The thickness of the porous film as a whole is the sum of the thickness of the first porous film and the second porous film on one main surface side of the negative electrode current collector, and the thickness of the third porous film described later.
[0038] The thickness of the first porous film (first thickness) can be greater than the thickness of the second porous film (second thickness). In this case, even if the expansion and contraction of the negative electrode occur repeatedly, the first porous film disposed on the separator side is not easily damaged. Therefore, the situation in which lithium metal enters the first porous film and precipitates in a dendrite shape is suppressed. The first thickness can be 1.1 times or more, 1.3 times or more, or 1.5 times or more relative to the second thickness.
[0039] The first thickness may be, for example, 0.1 μm to 2 μm, or 0.5 μm to 1 μm. The second thickness may be, for example, 0.1 μm to 1 μm, or 0.1 μm to 0.7 μm.
[0040] The thickness of the porous film can be obtained as the average value of the thicknesses at any five points in the cross section of the negative electrode. The thickness of the porous film is the length of the porous film in the thickness direction of the negative electrode.
[0041] An insulating third porous film may be disposed between the first porous film and the second porous film. The third porous film also has at least one through hole penetrating from the main surface on the separator side to the main surface on the negative electrode current collector side.
[0042] The third porous membrane may have two or more layers. The third porous membrane is formed, for example, of the above-mentioned insulating material. The thickness (third thickness) of the third porous membrane is not particularly limited. The third thickness may be appropriately set so that the thickness of the entire porous membrane reaches, for example, the above-mentioned range.
[0043] The negative electrode includes a negative electrode current collector made of a metal material that does not react with lithium metal.
[0044] As the metal material constituting the negative electrode current collector, for example, copper (Cu), nickel (Ni), iron (Fe), and alloys containing these metal elements can be listed. As alloys, copper alloys, stainless steel (SUS), etc. are preferred. As metal materials, copper and / or copper alloys are preferred from the perspective of conductivity. The copper content in the negative electrode current collector is preferably 50% by mass or more, and can be 80% by mass or more. The form of the metal material is, for example, foil. The thickness of the negative electrode current collector is not particularly limited, and is, for example, 5 μm to 20 μm.
[0045] [Method for producing porous film]
[0046] The porous film is formed by applying a raw material solution of the porous film on at least one main surface of the negative electrode collector. For example, the negative electrode is manufactured by a method having the following steps, wherein the steps are: a first step of preparing the negative electrode collector; a second step of drying the raw material solution (second raw material solution) of the second porous film on at least one main surface of the negative electrode collector to form the second porous film; and a third step of drying the raw material solution (first raw material solution) of the first porous film on the main surface of the negative electrode collector on which the second porous film is formed to form the first porous film.
[0047] When forming the third porous film, the fourth step is performed after the second step and before the third step, and the fourth step forms the third porous film by applying the raw material solution (third raw material solution) of the third porous film on the surface of the second porous film and then drying it. In this case, in the third step, the first raw material solution is applied to the main surface of the negative electrode collector via the second porous film and the third porous film.
[0048] Each raw material liquid contains, for example, the above-mentioned insulating material and a solvent. As the solvent, a good solvent having high compatibility with the insulating material used and a poor solvent having low compatibility with the insulating material used can be used. Alternatively, at least one of a lithium salt and a room temperature molten salt (hereinafter sometimes simply referred to as a salt) can be used together with the good solvent, wherein the good solvent is a solvent having high compatibility with the insulating material used.
[0049] When a good solvent and a poor solvent are used, in the coating film, the region containing the insulating material and the good solvent and the region containing the poor solvent are separated. Due to the separation, the region containing the poor solvent is configured to be sandwiched between the regions containing the insulating material. Next, drying is performed to remove the solvent, thereby forming through holes between the regions containing the insulating material, and forming non-through holes. For example, the pore size and porosity of the obtained porous film are controlled by the type of solvent and the mass ratio of the good solvent to the poor solvent.
[0050] When a good solvent and a salt are used, in the coating film, a region containing an insulating material, a good solvent and a salt and having a high concentration of the insulating material is separated from a region containing an insulating material and a good solvent and having a relatively low concentration of the insulating material. Next, drying is performed to remove the solvent, thereby forming through holes in a manner corresponding to the region with a relatively low concentration of the insulating material, and forming non-through holes. At this time, the salt remains in the porous film. For example, the pore size and porosity of the resulting porous film can be controlled by the type and concentration of the salt.
[0051] The good solvent and the poor solvent can be appropriately selected according to the insulating material used. When a good solvent and a poor solvent are used in combination, the boiling points of the good solvent and the poor solvent can differ by, for example, 10° C. or more from the perspective of easy pore formation. Examples of the solvent include N-methyl-2-pyrrolidone (NMP) and the like.
[0052] As the lithium salt, for example, a known lithium salt used for a non-aqueous electrolyte of a lithium secondary battery can be used. Specifically, as an anion of the lithium salt, BF4 - 、ClO4 - PF6 - CF3SO3 - CF3CO2 - , anions of oxalates, anions of imides described later as anions of room temperature molten salts, etc. The anions of oxalates may contain boron and / or phosphorus. The anions of oxalates may be anions of oxalate complexes. Examples of the anions of oxalates include difluorooxalate borate (BF2(C2O4) - ), bis(oxalate borate) (B(C2O4)2 - )、B(CN)2(C2O4) - PF4(C2O4) - PF2(C2O4)2 - The lithium salts may be used alone or in combination of two or more.
[0053] Room-temperature molten salt is a salt that is liquid at room temperature (20° C. to 40° C.), and is also called an ionic liquid.
[0054] From the viewpoint of facilitating the formation of pores, the room temperature molten salt may be a salt of an organic onium cation and an imide anion. The room temperature molten salt may be used alone or in combination of two or more.
[0055] Examples of the organic onium cation include cations derived from aliphatic amines, alicyclic amines, and aromatic amines (e.g., quaternary ammonium cations), nitrogen-containing onium cations such as organic onium cations having a nitrogen-containing heterocycle (i.e., cations derived from cyclic amines), sulfur-containing onium cations, phosphonium-containing onium cations (e.g., quaternary phosphonium cations), etc. The organic onium cation may have a functional group such as a hydroxyl group (-OH) or a silanol group (-Si-OH), and may have a divalent group derived from a silanol group (e.g., -SiO-).
[0056] Among them, from the viewpoint of heat resistance, it is preferred to have a cation containing a nitrogen-containing heterocyclic ring. As the nitrogen-containing heterocyclic skeleton, pyrrolidine, imidazoline, imidazole, pyridine, piperidine, etc. can be exemplified. Specifically, for example, N-methyl-N-propylpiperidinium cation (N-methyl-N-propylpiperidinium cation), N,N,N-trimethyl-N-propylammonium cation (N,N,N-trimethyl-N-propylammonium cation), 1-methyl-1-propylpyrrolidinium cation (1-methyl-1-propylpyrrolidinium cation) can be cited.
[0057] Examples of imide anions include N(SO2C m F 2m+1 )(SO2C n F 2n+1 )(m and n are each independently an integer greater than 0.) etc. m and n can be 0 to 3, and can be 0, 1 or 2. The anion of the imide can be a bistrifluoromethanesulfonyl imide anion (N(SO2CF3)2 - TFSI - ), bis(perfluoroethanesulfonyl)imide anion (N(SO2C2F5)2 - ), bis(fluorosulfonyl)imide anion (N(SO2F)2 - ). In particular, it can be bis(fluorosulfonyl)imide anion, TFSI - .
[0058] The concentration of the salt in the raw material solution is not particularly limited and may be appropriately set in consideration of the pore size and porosity of the porous membrane to be formed, etc. For example, the concentration of the salt may be 0.5% to 30% by mass, or 1% to 10% by mass.
[0059] The concentration of the insulating material in the raw material solution is not particularly limited and may be appropriately set in consideration of the thickness of the porous membrane to be formed, etc. The concentration of the insulating material may be, for example, 3% to 35% by mass, or 5% to 15% by mass.
[0060] [positive electrode]
[0061] The positive electrode includes a positive electrode current collector and a positive electrode mixture layer containing a positive electrode active material. The positive electrode mixture layer can be formed as follows: a positive electrode slurry formed by dispersing a positive electrode mixture containing a positive electrode active material, a binder, and a conductive agent in a dispersion medium is applied to the surface of the positive electrode current collector and dried. The dried coating film can be rolled as needed. The positive electrode mixture layer can be formed on one surface of the positive electrode current collector or on both surfaces.
[0062] As the positive electrode active material, a composite oxide containing lithium and a transition metal is used. The molar ratio of lithium to the transition metal contained in the composite oxide: lithium / transition metal is, for example, 0.9 to 1.1.
[0063] Examples of such positive electrode active materials include layered rock salt type composite oxides. Specifically, examples of positive electrode active materials include Li a CoO2、Li a NiO2、Li a MnO2、Li a Co b Ni 1-b O2、Li a Co b M 1-b O c , Li a Ni b M 1-b O c , LiMPO4, (M is at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B.) Here, 0<a≤1.1, 0≤b≤0.9, 2≤c≤2.3. It should be noted that the value a representing the molar ratio of lithium is the value immediately after the active material is produced, and will increase or decrease with charge and discharge.
[0064] Among them, a layered rock salt type composite oxide containing nickel is preferred. Such a composite oxide is Li a Ni x M 1-xO2 (M is at least one selected from the group consisting of Mn, Co and Al, 0<a≤1.1, 0.3≤x≤1.) From the viewpoint of high capacity, it is more preferred to satisfy 0.85≤x≤1. In addition, from the viewpoint of crystal structure stability, lithium-nickel-cobalt-aluminum composite oxide (NCA) containing Co and Al as M is further preferred: Li a Ni x Co y Al z O2 (0<a≤1.1, 0.85≤x<1, 0<y<0.15, 0<z≤0.1, x+y+z=1). Specific examples of NCA include LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.8 Co 0.18 Al 0.02 O2、LiNi 0.9 Co 0.05 Al 0.05 O2, etc.
[0065] Examples of the binder include resin materials such as fluororesins such as PTFE and PVdF; polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aramid resins; polyimide resins such as polyimide and polyamideimide; acrylic resins such as polyacrylic acid, polymethyl acrylate, and ethylene-acrylic acid copolymers; vinyl resins such as PAN and polyvinyl acetate; polyvinyl pyrrolidone; polyether sulfone; rubber-like materials such as styrene-butadiene copolymer rubber (SBR), etc. These may be used alone or in combination of two or more.
[0066] Examples of the conductive agent include graphites such as natural graphite and artificial graphite; carbon blacks such as acetylene black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; organic conductive materials such as phenylene derivatives, etc. These may be used alone or in combination of two or more.
[0067] The shape and thickness of the positive electrode current collector can be selected according to the shape and thickness of the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum (Al), aluminum alloy, and titanium.
[0068] [Non-aqueous electrolyte]
[0069] As the non-aqueous electrolyte, a non-aqueous electrolyte having lithium ion conductivity is used. Such a non-aqueous electrolyte contains a non-aqueous solvent and lithium ions and anions dissolved in the non-aqueous solvent. The non-aqueous electrolyte may be in a liquid state or in a gel state.
[0070] The liquid non-aqueous electrolyte can be prepared by dissolving a lithium salt in a non-aqueous solvent. The lithium salt dissolving in the non-aqueous solvent generates lithium ions and anions, but the non-aqueous electrolyte may contain a lithium salt that does not dissociate in the non-aqueous electrolyte.
[0071] The gel-like non-aqueous electrolyte comprises a liquid non-aqueous electrolyte and a matrix polymer. As the matrix polymer, for example, a polymer material that absorbs a non-aqueous solvent and gels is used. As such a polymer material, fluororesins, acrylic resins, and / or polyether resins can be cited.
[0072] As the lithium salt, a known lithium salt in a non-aqueous electrolyte for a lithium secondary battery can be used. Specifically, compounds exemplified as lithium salts used in the formation of a porous membrane can be cited. The non-aqueous electrolyte can contain one of these lithium salts, or two or more.
[0073] From the viewpoint of further suppressing the precipitation of lithium metal in the form of dendrites, the non-aqueous electrolyte may contain at least one of an imide anion and a boron-containing oxalate anion. Anions of boron-containing oxalate are particularly preferred. Anions of boron-containing oxalate may be used in combination with other anions. Other anions may be PF6 - and / or imide-type anions.
[0074] The concentration of the lithium salt in the non-aqueous electrolyte may be, for example, 0.5 mol / L or more and 3.5 mol / L or less. The concentration of the lithium salt is the sum of the concentration of the dissociated lithium salt and the concentration of the undissociated lithium salt. The concentration of the anion in the non-aqueous electrolyte may be set to 0.5 mol / L or more and 3.5 mol / L or less.
[0075] Examples of the non-aqueous solvent include esters, ethers, nitriles, amides, or halogen-substituted products thereof. The non-aqueous electrolyte may contain one of these non-aqueous solvents, or may contain two or more thereof. Examples of the halogen-substituted product include fluorides and the like.
[0076] As esters, for example, carbonates, carboxylates, etc. can be cited. As cyclic carbonates, ethylene carbonate, propylene carbonate, vinylene carbonate, fluoroethylene carbonate (FEC), etc. can be cited. As chain carbonates, dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate, etc. can be cited. As cyclic carboxylates, γ-butyrolactone, γ-valerolactone, etc. can be cited. As chain carboxylates, ethyl acetate, methyl propionate, methyl fluoropropionate, etc. can be cited.
[0077] Examples of the ether include cyclic ethers and chain ethers. Examples of the cyclic ether include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, and 2-methyltetrahydrofuran. Examples of the chain ether include 1,2-dimethoxyethane, ethyl ether, ethyl vinyl ether, methyl phenyl ether, benzyl ethyl ether, diphenyl ether, dibenzyl ether, 1,2-diethoxyethane, and diethylene glycol dimethyl ether.
[0078] Examples of the nitrile include acetonitrile, propionitrile, and benzonitrile, and examples of the amide include dimethylformamide and dimethylacetamide.
[0079] Among them, vinylene carbonate and fluoroethylene carbonate are preferred from the viewpoint of charge and discharge efficiency. Using these non-aqueous solvents sometimes easily generates dendrites. However, according to this embodiment, lithium metal is precipitated between the surface of the negative electrode collector and the second porous film when being squeezed by the porous film, so that dendrites are suppressed.
[0080] [Separator]
[0081] A separator is sandwiched between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous film, woven fabric, non-woven fabric, etc. can be used. As the material of the separator, polyolefins such as polypropylene and polyethylene are preferred.
[0082] [Lithium secondary battery]
[0083] Figure 3 This is a longitudinal cross-sectional view of an example of a cylindrical lithium secondary battery according to one embodiment of the present invention.
[0084] The lithium secondary battery 100 is a wound type battery including a wound electrode group 40 and a non-aqueous electrolyte (not shown). The wound electrode group 40 includes a strip-shaped positive electrode 10, a strip-shaped negative electrode 20, and a separator 30. A positive electrode lead 13 is connected to the positive electrode 10, and a negative electrode lead 23 is connected to the negative electrode 20.
[0085] One end of the positive lead 13 in the longitudinal direction is connected to the positive electrode 10, and the other end is connected to the sealing plate 90. The sealing plate 90 has a positive terminal 15. One end of the negative lead 23 is connected to the negative electrode 20, and the other end is connected to the bottom of the battery case 70 which serves as the negative terminal. The battery case 70 is a bottomed cylindrical battery can, one end of which is open in the longitudinal direction, and the bottom of the other end serves as the negative terminal. The battery case (battery can) 70 is made of metal, for example, iron. The inner surface of the iron battery case 70 is usually nickel-plated. An upper insulating ring 80 and a lower insulating ring 60 made of resin are respectively arranged above and below the wound electrode group 40.
[0086] The illustrated example illustrates a cylindrical lithium secondary battery with a wound electrode group, but the present embodiment is not limited to this case. The shape of the lithium secondary battery can be appropriately selected from various shapes such as cylindrical, coin-shaped, square, plate-shaped, flat, etc. according to its use. The shape of the electrode group is not particularly limited and can be a stacked type.
[0087] In addition, regarding the configuration of the lithium secondary battery other than the negative electrode, a known configuration can be used without particular limitation.
[0088] The present invention will be specifically described below based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0089] [Example 1]
[0090] (1) Preparation of positive electrode
[0091] Lithium nickel composite oxide (LiNi 0.8 Co 0.18 Al 0.02 O2), acetylene black and PVdF were mixed in a mass ratio of 95:2.5:2.5, NMP was added, and then stirred with a mixer (manufactured by PRIMIX Corporation, TKHIVIS MIX) to prepare a positive electrode slurry. Then, the positive electrode slurry was applied to the surface of the Al foil, the coating was dried, and then rolled to form a 3.6 g / cm2 film on both sides of the Al foil. 3 The positive electrode of the positive electrode mixture layer.
[0092] (2) Preparation of negative electrode
[0093] An electrolytic copper foil (10 μm thick) was cut into a predetermined electrode size, and a raw material solution containing PVdF (8% by mass concentration), LiTFSI (1% by mass concentration), and NMP was prepared.
[0094] The raw material solution was applied to both main surfaces of the electrolytic copper foil, and then hot air drying was performed to form a second porous membrane with a second thickness of 0.5 μm. The raw material solution was applied to the surfaces of the two second porous membranes in the same manner, and then hot air drying was performed to form a first porous membrane with a first thickness of 0.5 μm.
[0095] The cross section of the obtained negative electrode in the thickness direction was observed by SEM, and it was confirmed that a plurality of first through-holes with an average diameter of 800 nm were formed in the first porous film. Similarly, it was confirmed that a plurality of second through-holes with an average diameter of 800 nm were formed in the second porous film.
[0096] (3) Preparation of non-aqueous electrolyte
[0097] FEC, EMC and DMC were mixed at a volume ratio of FEC:EMC:DMC=20:5:75. Lithium difluorooxalate borate and LiPF6 were dissolved in the obtained mixed solvent to a concentration of 0.3 mol / L and 1.0 mol / L, respectively, to prepare a non-aqueous electrolyte.
[0098] (4) Battery production
[0099] An Al electrode sheet is installed on the positive electrode obtained in the above. An Ni electrode sheet is installed on the negative electrode obtained in the above. The positive electrode and the negative electrode are wound into a spiral shape with a polyethylene film (separator) sandwiched in an inactive atmosphere, thereby making a wound electrode body. The obtained electrode body is housed in a bag-shaped outer shell formed by a laminate sheet having an Al layer, the above-mentioned non-aqueous electrolyte is injected, and then the outer shell is sealed to make a lithium secondary battery T1.
[0100] [Example 2]
[0101] In the preparation (2) of the negative electrode, a lithium secondary battery T2 was prepared in the same manner as in Example 1 except that the first thickness of the first porous film was set to 1 μm.
[0102] [Example 3]
[0103] A lithium secondary battery T3 was produced in the same manner as in Example 1 except that a third porous film consisting of two layers (third thickness: 1 μm=0.5 μm×2) was formed between the second porous film and the first porous film in the production of the negative electrode (2).
[0104] [Comparative Example 1]
[0105] A lithium secondary battery R1 was produced in the same manner as in Example 1 except that the same raw material solution was used to form a porous film having a thickness of 2 μm in the production of the negative electrode (2).
[0106] The cross section of the obtained negative electrode in the thickness direction was observed by SEM, and it was confirmed that a large number of through holes with an average diameter of 800 nm were formed in the formed porous film.
[0107] [Comparative Example 2]
[0108] A lithium secondary battery R2 was produced in the same manner as in Example 1 except that a raw material solution containing no LiTFSI was used in the production (2) of the negative electrode.
[0109] The cross section of the obtained negative electrode in the thickness direction was observed by SEM, and it was found that both the formed two-layer films were non-porous films having no through-holes.
[0110] [evaluate]
[0111] The obtained batteries T1 to T3, R1, and R2 were subjected to charge and discharge tests.
[0112] In the charge and discharge test, the battery was charged in a thermostatic chamber at 25° C. under the following conditions, then rested for 20 minutes and discharged under the following conditions. This charge and discharge was regarded as one cycle, and the charge and discharge test was performed 50 times.
[0113] (Charging) Perform constant current charging at a current of 20 mA until the battery voltage reaches 4.1 V, and then perform constant voltage charging at a voltage of 4.1 V until the current value reaches 2 mA.
[0114] (Discharge) Perform constant current discharge at a current of 20 mA until the battery voltage reaches 3.0 V.
[0115] (a) Lithium metal deposition location and (b) negative electrode damage
[0116] After 50 cycles of charge and discharge, the battery was disassembled and the negative electrode was taken out. The negative electrode was cut along the thickness direction and the cross section was observed using a scanning electron microscope (SEM). The evaluation results are shown in Table 1. Figure 4A A SEM image (magnification: 2500 times) of a cross section of a negative electrode taken out from battery T1 is shown. Figure 4B Will Figure 4A A portion of the SEM image is enlarged and shown. Figure 4B In FIG. 1 , the interface between the first porous membrane 22A and the second porous membrane 22B is shown by a dotted line for convenience. Figure 4A and Figure 4B , lithium metal (Li) is precipitated between the negative electrode current collector 21 and the second porous membrane 22B. Figure 5 FIG. 2 shows a SEM image (magnification 2500 times) of a cross section of a negative electrode taken out of battery R1. Figure 5 Lithium metal (Li) is deposited on the main surface of the porous film 22 that does not face the negative electrode current collector 21 (the main surface on the separator side not shown).
[0117] (c) Capacity maintenance rate
[0118] The value obtained by dividing the discharge capacity at the 50th cycle by the discharge capacity at the 1st cycle was defined as the capacity retention rate (%). The evaluation results are shown in Table 1.
[0119] [Table 1]
[0120]
[0121] As shown in Table 1, in batteries T1 to T3, the precipitation position of lithium metal is controlled between the negative electrode collector and the second porous membrane, and the capacity retention rate is also high. On the other hand, in batteries R1 and R2, the porous membrane or the non-porous membrane is damaged, and lithium metal is precipitated between each membrane and the separator. Moreover, part of the precipitated lithium metal is in the form of dendrites. In addition, the capacity retention rate is lower than that of batteries T1 to T3.
[0122] Industrial Applicability
[0123] The lithium secondary battery of the present invention has excellent discharge capacity and cycle characteristics and can be used in electronic devices such as mobile phones, smartphones, and tablet terminals, electric vehicles including hybrid vehicles and plug-in hybrid vehicles, and household storage batteries combined with solar cells.
[0124] Description of Reference Numerals
[0125] 10 Positive electrode
[0126] 13 Positive lead
[0127] 15 Positive terminal
[0128] 20 Negative electrode
[0129] 21. Negative electrode current collector
[0130] 22A No. 1 porous membrane
[0131] 22B Second porous membrane
[0132] 23 Negative lead
[0133] 30 Dividers
[0134] 40 Wound Electrode Group
[0135] 60 Lower insulation ring
[0136] 70 Battery housing
[0137] 80 Upper insulation ring
[0138] 90 Sealing plate
[0139] 100 Lithium secondary battery
[0140] 22 porous membrane
Claims
1. A lithium secondary battery comprising a positive electrode, a negative electrode, a lithium ion conductive non-aqueous electrolyte, and a separator disposed between the positive electrode and the negative electrode, The positive electrode comprises a positive electrode current collector and a positive electrode mixture layer containing a positive electrode active material. The positive electrode active material includes a composite oxide containing lithium and a transition metal. The total amount M of lithium per unit area of the positive electrode and the negative electrode Li The transition metal amount M per unit area of the positive electrode TM Molar ratio: M Li / M TM is below 1.1, The negative electrode comprises a negative electrode current collector and a plurality of insulating porous films stacked on the negative electrode current collector. The plurality of insulating porous films are in contact with each other, The plurality of porous films include a first porous film and a second porous film disposed between the first porous film and the negative electrode current collector, wherein an average diameter of through-holes of the second porous film is smaller than an average diameter of through-holes of the first porous film.
2. The lithium secondary battery according to claim 1, wherein The thickness of the first porous membrane is equal to or greater than the thickness of the second porous membrane.
3. The lithium secondary battery according to claim 1 or 2, wherein: The first porous film has a thickness of 0.1 μm or more and 2 μm or less, The second porous film has a thickness of 0.1 μm or more and 1 μm or less.
4. The lithium secondary battery according to claim 1 or 2, wherein: Each of the plurality of porous films has a region facing the positive electrode mixture layer. At least one of the plurality of porous films has a non-opposing region that does not oppose the positive electrode mixture layer. At least a portion of the non-opposing region is in contact with the negative electrode current collector in a charged state.
5. The lithium secondary battery according to claim 1 or 2, wherein: At least one of the plurality of porous membranes includes a polymer having a unit derived from vinylidene fluoride.
6. The lithium secondary battery according to claim 1 or 2, wherein: At least one of the plurality of porous films contains at least one of a lithium salt and a room-temperature molten salt.
7. The lithium secondary battery according to claim 1 or 2, wherein: The nonaqueous electrolyte includes at least one of fluoroethylene carbonate and vinylene carbonate.
8. The lithium secondary battery according to claim 1 or 2, wherein: The nonaqueous electrolyte comprises lithium ions and anions, The anion includes at least one of an imide-based anion and a boron-containing oxalate-based anion.
9. The lithium secondary battery according to claim 8, wherein: The imide anion is at least one of a bis(fluorosulfonyl)imide anion and a bistrifluoromethanesulfonyl imide anion.
Citation Information
Patent Citations
Protective film, separator using same, and secondary battery
WO2015030230A1
Plating technique for electrode
US20130017441A1
Negative electrode for lithium metal battery and lithium metal battery comprising the same
US20170317352A1
Lithium metal battery
US20170331152A1